Electrical circuit theory and technology - Bird, J. O. (Newnes, 2010)
Now in its third edition, this best-selling textbook has been updated with developments in key areas such as semiconductors, transistors, and fuel cells, along with brand new material on ABCD parameters and Fourier's Analysis. Greater emphasis is placed on real-world situations in order to ensure the reader can relate the theory to actual engineering practice. In addition, the text has been restructured throughout so that 175 Exercises now appear at regular intervals, which the student can work through to test their learning of essential concepts and check their progress.